Pengaruh Hedonic Shopping Value Dan Shopping Lifestyle Akan Impulse Buying Behavior Melalui Positive Emotion Sebagai Variabel Intervening (Studi Kasus Bagi Pengunjung Mall Olympic Garden Malang) - Miftakhul Nurjanah; Siti Asiyah; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study is the result of conducting a survey on the hedonic amount of shopping and shopping life influences the impact of improving the behavior of visitors in the Malang Olympic Mall with positive emotions as a mediating variable. The survey was conducted in the city of Malanga with a sample of 75 respondents. The sampling technique used in this study is non-probability sampling and the type of sampling is convenience sampling. Data collection methods were completed by those who sent barcoded questionnaires and measured 15 indicators using a 5-point Likert scale. The data analysis technique used to answer the hypotheses was Smart PLS software constructed using 4 latent variables and reflective indicators. The results of this study show that (1) The hedonic value of shopping has a positive and significant impact on positive emotions. (2) The shopping lifestyle has a great positive influence on positive emotions. (3) Positive emotions have a significant positive influence on impulse buying behavior. (4) The hedonic value of a purchase has a positive impact on purchasing behavior. (5) Shopping lifestyle has a positive and negligible influence on positive emotions. (6) The intervention variable value of successful shopping has a great influence on impulsive buying behavior through positive emotions. (7) Shopping lifestyle has a great influence on impulsive buying behavior with positive emotions as a mediating variable. Keywords: Hedonic Shopping Values, Shopping Lifestyle, Impulse Buying Behavior, and Positive Emotions